Identification of new process-related impurity in the key intermediate in the synthesis of TCV-116 - Testen Ana; Plevnik Miha; Štefane Bogdan; Cigić Irena Kralj (Acta Pharmaceutica)
Development of safe and effective drugs requires complete impurity evaluation and, therefore, knowledge about the formation and elimination of impurities is necessary. During impurity profiling of a key intermediate during synthesis of candesartan cilexetil (1-(((cyclohexyloxy)carbonyl) oxy)ethyl 1-((2’-(2H-tetrazol-5-yl)-[1,1’-biphenyl]-4-yl) methyl)-2-ethoxy-1H-benzo[d]imidazole-7-carboxylate, TCV-116), a novel compound, which had not been reported previously, was observed. Structural elucidation of impurity was achieved by liquid chromatography hyphenated to different high resolution mass analyzers. Based on exact mass measurements and fragmentation pattern, a chloro alkyl carbonate ester analogue of the intermediate was identified. Structure of the impurity was confirmed by mass spectro-metric and NMR analyses of the target substance. Identified impurity could represent a hazard if it is transferred to the final API stage and its presence should be kept below allowed limits. Further investigation could reveal whether bis(1-chloroethyl) carbonate is a precursor to impurity formation. Therefore, synthesis should be regulated so as to minimize impurity production. Analysis of the final product indicated that the amount of impurity did not exceed 50 mg L−1, which represents the detection limit, determined according to the signal/noise ratio.